'The million-dollar question' – exploring teachers and ETB staff understanding of characteristic spirit in publicly managed schools in Ireland. Issue 1 (2nd January 2019) - Liddy, Mags; O'Flaherty, Joanne; McCormack, Orla
Abstract : Using a mixed methods approach this study explores characteristic spirit in the post-primary publicly managed sector as understood by teachers and key school personnel of Education and Training Board (ETB) schools and ETB staff. Prior to the Education Act (1998), characteristic spirit did not apply to the ETB sector, resulting in an absence of related policy within the sector. This paper, drawing on questionnaire ( n = 126) and interview data ( n = 73), focuses on research participants' understanding of characteristic spirit and how they see it expressed in their schools. Uncertainty around the meaning of characteristic spirit was common with over half of teacher respondents rating their level of understanding as average or below. Participants frequently found it difficult to articulate their understanding, even questioning its relevance and applicability to the ETB sector. When asked to illustrate the application of characteristic spirit in their own schools, many referred to the relational, implicit and lived nature of characteristic spirit. Furthermore, some participants believed that values played an important part in articulating a characteristic spirit for the ETB. The paper concludes by exploring some reasons for teacher uncertainty around characteristic spirit and proposes some possible future directions with regard to ETB characteristic spirit.